Pengaruh Metode Pembelajaran dan Motivasi Belajar terhadap Kemampuan Menulis Anekdot pada Siswa Kelas X Madrasah Aliyah Swasta di Kota Depok - titi sukarti (SAP (Susunan Artikel Pendidikan), 2019)
The purpose of this research is to find the influence of a method of learning in the ability of the students write the text of anecdotes private Madrasah Aliyah Depok city .The influence of the motivation to study write the text of anecdotes students in the ability of the private Madrasah Aliyah Depok city .The influence of interactive method of learning and the motivation to study write the text of anecdotes students in the ability of the private Madrasah Aliyah Depok city .Research methods that were used is the experimental methods are .It is a whole research population in a student of class x ma private in Sukmajaya Depok city, namely Madrasah Aliyah Nur Al Zahrah and Madrasah Aliyah Al Jihad in the academic year 2016-2017, where the capacity of each individual class between the 34-40 students. While the total sample that is the draw (parallel from the total number of classrooms to school population) 65 students .The research results show: 1) Significant influence in the ability of the method of learning write the text of anecdotes students MA Nur Al Zahrah. 2) Significant influence in the ability of the the motivation to study write the text of anecdotes students in MA Nur Al Zahrah. 3) There are the influence of the interaction that significant a method of learning and the motivation to study of the ability of students write the text of anecdotes MA Nur Al Zahrah. The impact of this method that is obtained from the teaching process increases significantly every aspects of attention , active, exited , and conducive students toward the direction of the better. To motivate your students in order to want to write the text of anecdotes through a method of interactive learning and so students can be more active in developing ideas in writing text anecdote.